2015
DOI: 10.1007/s10029-015-1400-7
|View full text |Cite
|
Sign up to set email alerts
|

Inguino-scrotal herniation of the ureter containing stones

Abstract: A herniated ureter is potentially a source of serious renal or ureteral complications. When discovered, ureteric hernias should be surgically repaired. If preoperative detection of a ureter herniation alongside an inguinal hernia is missed, awareness of the existence of this condition may help avoid iatrogenic ureteral damage injury during a complex hernioplasty. Documentation of unexplained, sizeable and distinct calcifications in an inguino-scrotal hernia sac, particularly in a patient with a history of urol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…Previous studies have demonstrated that 42% of cases are inguinoscrotal in nature [13] , [15] . Ureteric hernias can also be cited as spontaneous, postoperative, or as a complication of renal transplant surgery [13] , [14] There are 2 anatomic presentations of ureteral herniation that have been reported in the literature: paraperitoneal and extraperitoneal herniations [5] , [6] , [14] , [17] , [18] , [19] . The vast majority of cases are of the paraperitoneal type which accounts for 80% of them [5] , [6] .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have demonstrated that 42% of cases are inguinoscrotal in nature [13] , [15] . Ureteric hernias can also be cited as spontaneous, postoperative, or as a complication of renal transplant surgery [13] , [14] There are 2 anatomic presentations of ureteral herniation that have been reported in the literature: paraperitoneal and extraperitoneal herniations [5] , [6] , [14] , [17] , [18] , [19] . The vast majority of cases are of the paraperitoneal type which accounts for 80% of them [5] , [6] .…”
Section: Discussionmentioning
confidence: 99%
“…Ureteric hernias can also be cited as spontaneous, postoperative, or as a complication of renal transplant surgery [13] , [14] There are 2 anatomic presentations of ureteral herniation that have been reported in the literature: paraperitoneal and extraperitoneal herniations [5] , [6] , [14] , [17] , [18] , [19] . The vast majority of cases are of the paraperitoneal type which accounts for 80% of them [5] , [6] . This anatomic variant is defined by a ureter that is posteriorly attached to an indirect peritoneal hernia sac resulting in it sliding beside it [5] This type of hernia is most commonly associated with the herniation of other organs, often the colon [5] , [6] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations